Reassessing neurodegenerative disease: immune protection pathways and antagonistic pleiotropy. Issue 10 (October 2021) - Provenzano, Francesca; Deleidi, Michela
Abstract : The antagonistic pleiotropy (AP) theory posits that adaptive evolutionary changes, which facilitate reproduction and individual fitness early in life, can enhance detrimental aging-related processes. Several genes associated with human brain diseases play a protective role in infection, suggesting the relevance of AP in the context of brain aging and neurodegeneration. Relatedly, genetic variants that confer immune protection against pathogens may lead to uncontrolled brain inflammation later in life. Here, we propose a conceptual framework suggesting that the pleiotropic roles of genes in infections and host–pathogen interactions should be considered when studying neurological illnesses. We reinterpret recent findings regarding the impact of neurological disease-associated genetic traits on infections and chronic inflammatory diseases. Identifying the AP pathways shared among these seemingly unrelated conditions might provide further insights into the detrimental role of the immune system in brain disease as well as the mechanisms involved in chronic infections. Highlights: Genetic susceptibility to neurological disease is frequently associated with immune defense against pathogens, and these associations often demonstrate antagonistic pleiotropy effects. While effective immune responses are required for pathogen clearance, strongly dysregulated and persistent inflammatory reactions may be detrimental to nervous system homeostasis. Further dissecting the factors that contribute to the early interaction between host and pathogen, as well as those that participate in chronic infections, may provide insight into the mechanisms underlying the disruption of the balance between protective and pathogenic immune responses. Combining integrative genetic approaches with analyses of immune cell phenotypes as well as novel multiorgan cellular models will provide information about individual inflammatory risk. Understanding the relationship between infection and brain disease risk might guide immunotherapy for nervous system disorders as well as the development of host-based strategies for the eradication of antibiotic-resistant and persistent bacteria.